2019
DOI: 10.31590/ejosat.618341
|View full text |Cite
|
Sign up to set email alerts
|

Analitik Kimya Laboratuvarında Sorgulama Temelli Sistematik Kalitatif Katyon Analizi Deneylerinin Bilimsel Süreç Becerilerine Yansıması

Abstract: The theoretical knowledge and practice are connected through deep thinking and reflection during the research and inquiry process in the laboratory environment. Throughout the inquiry-based experiments, students can make this connection by developing their science process skills. In this respect, the aim of this study is to examine the development of students' science process skills in the Systematic Qualitative Analysis of Cation (SQAC) experiments conducted using I diagram tool. This research was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
(20 reference statements)
0
3
0
1
Order By: Relevance
“…Similarly, a significant and positive relationship was found between pre-service science teachers' laboratory course success and their perceptions of science process skills (β= .27 p> .01). Various studies have showed that laboratories enable individuals to develop their scientific process skills (Akkuzu Güven and Uyulgan, 2019;George-Williams et al, 2020;Irwanto et al, 2019). At the same time, it can be stated that the basic skills required for laboratory activities to achieve their objectives are science process skills.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, a significant and positive relationship was found between pre-service science teachers' laboratory course success and their perceptions of science process skills (β= .27 p> .01). Various studies have showed that laboratories enable individuals to develop their scientific process skills (Akkuzu Güven and Uyulgan, 2019;George-Williams et al, 2020;Irwanto et al, 2019). At the same time, it can be stated that the basic skills required for laboratory activities to achieve their objectives are science process skills.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Permanent learning occurs when inquiries are made during education. In particular, some studies in the literature reveal that individuals who can actively engage their science process skills during the inquiry process can achieve effective, easy and permanent learning by their own efforts (Akkuzu Güven & Uyulgan, 2019;Duschl et al, 2007;NRC, 2012). Settlage and Southerland (2007) emphasize that science process skills form a basis for inquiry.…”
Section: The Relationship Between Inquiry Skills and Science Process ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Günümüz bilgi çağıdır. Bu çağda yeni bilgiler üretme ve teknolojiye ayak uydurma önemli bir beceri haline gelmiştir (Akkuzu ve Uyulgan, 2019). Öğrencilerin bu becerileri kazanabilmesi için okulların, derslerde kullanılan öğretim yöntemleri ve teknikleri, eğitim ortamı, okul iklimi, okula bağlılık ve iletişim gibi birçok açıdan değerlendirilmesi gerekir.…”
Section: Introductionunclassified